Halal Certification Assistance for Sambal Pecel Madiun Ikopin MSMEs in Jatinangor, Sumedang, Indonesia - Gina Firgianti (Research Collaboration Community (Rescollacom), 2025)
Sambal pecel is a traditional Indonesian plant-based food product that falls under the low-risk category for halal certification. This study aims to describe the halal certification assistance process provided to the Sambal Pecel Madiun Ikopin MSME through the self-declare scheme. The four-week program included halal literacy education, technical assistance for uploading documents to the SIHALAL system, and verification by an official halal facilitator (PPH assistant). As a result, the MSMEs successfully fulfilled all administrative and technical requirements and obtained a halal certificate. The assistance proved effective in enhancing MSMEs actors’ understanding of halal regulations and their readiness in preparing legal documents such as NIB, halal ingredient lists, and production segregation. The study also highlights challenges including limited digital literacy and user-unfriendly system interfaces. The success of this program not only resulted in halal certification but also improved product competitiveness, consumer trust, and market opportunities. This study recommends a sustainable mentoring model through collaboration between universities, PPH assistants, and BPJPH to expand access to halal certification for MSMEs effectively. Keywords: halal certification, self-declare, MSMEs, sambal pecel, halal mentoring